THE IMPACT OF CHATGPT USAGE ON STUDENTS’ ACADEMIC PERFORMANCE - Munkhsaikhan, Tserenpurev; Dalkhjav, Battsetseg (Journal of Business and Innovation (Бизнес & Инноваци), 2025)
This study examines the impact of using ChatGPT on the academic performance of students at the Business School of the National University of Mongolia (NUM). As artificial intelligence (AI) and digital technologies become more integrated into education, tools like ChatGPT have emerged as valuable resources for students, providing personal assistance, quick access to information, and support in understanding complex topics. The research focuses on undergraduate students, exploring how ChatGPT influences their learning motivation and academic performance. The findings reveal that ChatGPT usage has a positive and significant impact on both learning motivation (β=0.233) and academic performance (β=0.254). Additionally, learning motivation was found to mediate the relationship between ChatGPT usage and academic performance. This study contributes to the growing body of literature on AI in education, particularly within the context of higher education in Mongolia. It also offers practical recommendations for educators and policymakers.